GRECHUTA: A POET, COMPOSER, TEACHER AND MENTOR AN ATTEMPT AT CHARACTERISTICS OF HIS ARTISTIC OEUVRE - Piotrowska, Anna G. (Literatura Ludowa. Journal of Folklore and Popular Culture, 2017)
An architect by profession, a painter in his free time, and primarily known as a composer, songwriter and singer, Marek Grechuta (1945-2006) fully deserves to be called an artist with many faces. His musical landscape dazzles with colours of vocal voices and solo instruments. Sensitivity to the word and the subtle shading of musical and textual nuances are his other distinctive features. As a charismatic performer, he undoubtedly created his own artistic style, which combines specific musical features, unique performance and esoteric poetics. Due to the universality of his music, his songs are still cherished and willingly listened to by new generations.